2008
DOI: 10.4238/vol7-1gmr367
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in the Pantaneiro horse breed assessed using microsatellite DNA markers

Abstract: AbSTRAcT. The genetic variability for a sample of 227 animals from three populations of Pantaneiro horses was estimated using data from 10 microsatellite loci. The number of alleles and the proportion of heterozygosity indicated high variability. A total of 91 alleles were found, with a significantly high mean number of alleles. The mean polymorphic information content was 0.7 and the paternity exclusion probability was 99.3%. The inbreeding coefficient (F IS ) was low for the three populations: Ipiranga (F IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
4
22
2
Order By: Relevance
“…Intermediate values, similar to those reported here for the MM breed, were also described for Lippizan (0.663), Sable Island (0.626), and Anglo-Arab (0.66) horses (Kelly et al, 2002;Tozaki et al, 2003;Achmann et al, 2004;Luís et al, 2002Luís et al, , 2005Plante et al, 2007). Recently, a relatively high mean PIC (0.700) was reported for the Pantaneiro horse, an endangered Brazilian feral horse breed (Giacomoni et al, 2008 Table 2. Wright F-statistics.…”
Section: Discussionsupporting
confidence: 83%
“…Intermediate values, similar to those reported here for the MM breed, were also described for Lippizan (0.663), Sable Island (0.626), and Anglo-Arab (0.66) horses (Kelly et al, 2002;Tozaki et al, 2003;Achmann et al, 2004;Luís et al, 2002Luís et al, , 2005Plante et al, 2007). Recently, a relatively high mean PIC (0.700) was reported for the Pantaneiro horse, an endangered Brazilian feral horse breed (Giacomoni et al, 2008 Table 2. Wright F-statistics.…”
Section: Discussionsupporting
confidence: 83%
“…When we look at native horses all over the world, most of them are on the verge of extinction [13]. The Kiso horse experienced rapid loss of the population causing a bottleneck, which we confirmed here, and is categorized as one of such endangered breeds [27,28].…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, some efforts have made by breeder associations or governments to conserve native horses based on scientific ways [4,13,27]. Similarly, we started to work with the Kiso Horse Conservation Association to create a management program for conservation, and studied the genetic diversity of the Kiso horse in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the high polymorphism found among Criollo horses in this study is striking, even more so when one compares the average number of alleles per locus with other national (Luis et al, 2007b) and foreign herds (Kelly et al, 2002;Luis et al, 2007b;Paredes et al, 2009), or even other breeds (Bowling et al, 1997;Jakabová, 2002;Solis et al, 2005;Lee and Cho, 2006;Kakoi et al, 2007;Luis et al, 2002Luis et al, , 2007aPlante et al, 2007;Giacomoni et al, 2008;Perez-Gutierrez et al, 2008;Thirstrup et al, 2008;Bomcke and Gengler, 2009;LeRoy et al, 2009). This particularity can be attributed to the short period since the closing of its stud book or the constant migration of animals (Thirstrup et al, 2008) solely allowed between countries affiliated with FICCC.…”
Section: Discussionmentioning
confidence: 59%
“…Deviation from Hardy-Weinberg equilibrium and heterozygote deficit were already described in previous publications evaluating Criollo horses (Kelly et al, 2002;Luis et al, 2007b;Paredes et al, 2009), but never in all the reported loci shown by a single study. In several other horse breeds, small differences were also described (Jakabová, 2002;Solis et al, 2005;Lee and Cho, 2006;Kakoi et al, 2007;Luis et al, 2002Luis et al, , 2007aGiacomoni et al, 2008;Perez-Gutierrez et al, 2008;Thirstrup et al, 2008).…”
Section: Discussionmentioning
confidence: 95%